Index of the Project Gutenberg Works of Ambrose Bierce - Bierce, Ambrose, 1842-1914?; Widger, David, 1932-2021? (Salt Lake City, UT : Project Gutenberg, 2019)
"Index of the Project Gutenberg Works of Ambrose Bierce" by Ambrose Bierce is a compilation of literary works belonging to the author, categorized and organized for easier access. This book, which serves as a bibliographic resource, was composed during the early 20th century. It includes a diverse array of Bierce's writings, ranging from short stories to essays and satirical pieces, showcasing his unique voice and style in literature. The compilation includes beloved works like "The Devil's Dictionary" and "An Occurrence at Owl Creek," alongside various essays and short stories that reflect Bierce's sharp wit and cynicism. It captures themes such as the absurdities of life, moral complexities, and social critiques, which are prevalent throughout his writing. The index provides readers with a comprehensive guide to Bierce's works, great for those interested in exploring his contributions to American literature and understanding his distinctive perspective on human nature and societal norms. (This is an automatically generated summary.)
Release date is 2019-02-01
Produced by David Widger
Keywords: Indexes